2006
DOI: 10.1080/15476910601023602
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Bis(tri-n-butyltin)oxide (TBTO)-Induced Immunotoxicity in Mice and Rats

Abstract: Bis(tri-n-butyltin)oxide (TBTO) is one of the organotin compounds that have been used as biocides and occur as persistent environmental pollutants. Human exposure to these compounds occurs through consumption of meat and fish products in which they accumulate. The most sensitive endpoint of TBTO exposure is immunotoxicity. TBTO causes thymus atrophy and thereby interferes with T-lymphocyte-mediated immune responses. Tributyltin compounds have been found to adversely affect a wide range of cellular components a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 88 publications
(100 reference statements)
0
24
0
Order By: Relevance
“…Induction of thymocyte apoptosis by TBTO appeared to precede inhibition of cell proliferation, since the former was found after short exposure times in vitro, whereas the latter was the main finding at later time points during in vitro and in vivo studies [111]. Administration of a high dose of TBTO to mice resulted in significant regulation of gene expression in the thymus, whereas absence of overt gene expression changes was found in rat thymus after exposure to a somewhat lower dose, even though immunotoxic effects were observed as indicated by the involution of this organ [134].…”
Section: Immunotoxicogenomicsmentioning
confidence: 98%
“…Induction of thymocyte apoptosis by TBTO appeared to precede inhibition of cell proliferation, since the former was found after short exposure times in vitro, whereas the latter was the main finding at later time points during in vitro and in vivo studies [111]. Administration of a high dose of TBTO to mice resulted in significant regulation of gene expression in the thymus, whereas absence of overt gene expression changes was found in rat thymus after exposure to a somewhat lower dose, even though immunotoxic effects were observed as indicated by the involution of this organ [134].…”
Section: Immunotoxicogenomicsmentioning
confidence: 98%
“…Several studies have successfully demonstrated expression changes and their casual relation with representative responses in identifying immunotoxicity potentials of CONTACT Rajesh Mandarapu rajeshmandarapu@yahoo.com #2/14, G.K. Flats, G2, 1st Main Road, North Sriramnagar, West Tambaram, Chennai, Tamil Nadu, India various agents (Zeytun et al 2002;Kinser et al 2004;Baken et al 2006Baken et al , 2007aBaken et al ,b, 2008. Similarly, gene expression profiling studies conducted in tissues/cells such as the liver, spleen, thymus, lymph nodes and peripheral blood lymphocytes also proved useful in predictive risk assessment (Bulera et al 2001;Thomas et al 2001;Waring et al 2001;Hamadeh et al 2002a,b;Steiner et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have been performed on TBTO toxicity in different species as well as in vitro systems and the molecular mechanisms underlying its toxicity have been investigated, amongst others using DNA microarrays (Baken et al, 2006;Baken et al, 2007), details of its mechanism of toxicity still remain elusive. For instance, none of the proposed mechanisms based on indirect effects, such as metabolic disturbance, stress-induced glucocorticoid lymphocytolysis, etc., to explain the observed thymus involution has been considered satisfactory (Raffray and Cohen, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, none of the proposed mechanisms based on indirect effects, such as metabolic disturbance, stress-induced glucocorticoid lymphocytolysis, etc., to explain the observed thymus involution has been considered satisfactory (Raffray and Cohen, 1993). Alternative mechanisms such as apoptosis (Raffray and Cohen, 1993) and the anti-proliferative effect of TBTO 1997;Vandebriel et al, 1999) have been suggested to account for the triorganotin-induced thymic involution, but, to date, the molecular events leading to these processes remain unclear (Raffray and Cohen, 1993;Gennari et al, 1997;Vandebriel et al, 1999;Baken et al, 2006). Therefore, in order to get more insight into the mechanisms of TBTO toxicity we undertook proteomic analysis of the EL4 thymoma cell line exposed to TBTO and compared quantitatively the proteome of TBTO-exposed to non-exposed (control) cells.…”
Section: Introductionmentioning
confidence: 99%